2021
DOI: 10.1371/journal.pone.0255933
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing in childhood-onset epilepsies: Diagnostic yield and impact on neuronal ceroid lipofuscinosis type 2 (CLN2) disease diagnosis

Abstract: Epilepsy is one of the most common childhood-onset neurological conditions with a genetic etiology. Genetic diagnosis provides potential for etiologically-based management and treatment. Existing research has focused on early-onset (<24 months) epilepsies; data regarding later-onset epilepsies is limited. The goal of this study was to determine the diagnostic yield of a clinically available epilepsy panel in a selected pediatric epilepsy cohort with epilepsy onset between 24–60 months of life and evaluate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…TPP1 variants were the second most common in this cohort tested through the Epilepsy and Genetics Program, only less frequent than SCN1A variants ( Table 1 ). The proportion of TPP1 variants was lower than the one found by Gall et al 21 and higher than the one found by Leal-Pardinas et al 17 These differences observed between the studies are probably related to the genetic background of each population and/or different inclusion criteria.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…TPP1 variants were the second most common in this cohort tested through the Epilepsy and Genetics Program, only less frequent than SCN1A variants ( Table 1 ). The proportion of TPP1 variants was lower than the one found by Gall et al 21 and higher than the one found by Leal-Pardinas et al 17 These differences observed between the studies are probably related to the genetic background of each population and/or different inclusion criteria.…”
Section: Discussioncontrasting
confidence: 59%
“…In these cases, it is recommended that the clinician should order an epilepsy gene panel to narrow down diagnostic possibilities. 15 Pathogenic or likely-pathogenic TPP1 variants are a relatively common finding in NGS panels performed to investigate pediatric seizures, [21][22][23] emphasizing that these genetic panels can be a very useful tool to confirm or exclude CLN2 diagnosis and, if confirmed, provide disease-specific treatment for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common clinical manifestations is epilepsy. It could occur at any age, often during the first decade but sometimes in the second or third decade and become therapy resistant [ 10 ]. Heterozygous females with germline missense or nonsense DCX variants may have no obvious brain malformations or seizures [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…interacts with ATP2B2 (ATPase, Ca (2+)-Transporting, Plasma membrane, 2, MIM 108733) 55,59 , variants of which are found in patients with autism spectrum disorder 58,117 . KCNA2 (Potassium Channel, Voltage-Gated, Shaker-Related Subfamily, Member 2, MIM 176262) interacting with FAR2 55 , is associated with epileptic encephalopathy 118 and epilepsy [119][120][121][122] . Another FAR2 interacting protein, CUL3, is associated with neurodevelopmental disorders 77 and autism spectrum disorder 50 .…”
Section: Ints13 (Integratormentioning
confidence: 99%